Differences in PD-L1–Expressing Macrophages and Immune Microenvironment in Testicular Germ Cell Tumors. Issue 3 (5th December 2019) - Sadigh, Sam; Farahani, Sahar J; Shah, Abhishek; Vaughn, David; Lal, Priti
Abstract: Objectives: To characterize the tumor microenvironment of testicular germ cell tumors (GCTs) using immunohistochemical markers. Methods: Seventy-seven orchiectomies, including 36 nonmetastatic (NM) seminomas, 15 metastatic (M) seminomas, 13 nonmetastatic nonseminomatous germ cell tumors (NSGCTs), and 13 metastatic NSGCTs, were studied with PD-1, PD-L1, FOXP3, CD68, CD163, and mismatch repair (MMR) immunohistochemistry. FOXP3+ and PD-1+ tumor-infiltrating lymphocytes (TILs) and tumor-associated macrophages (TAMs) expressing CD68 and CD163 were enumerated. PDL-1 expression was evaluated on tumor cells and macrophages. Results: GCTs primarily express PD-L1 on TAMs, except choriocarcinoma, where true tumor cell positivity was noted. Seminomas reveal increased intratumoral PD-L1+ TAMs compared with NSGCTs ( P < .05). Activated TILs are increased in NM-seminomas compared with M-seminomas ( P < .05). All GCTs retained MMR expression. Conclusions: Robust PD-L1+ TAMs are significantly expanded in seminomas compared with NSGCTs. Among all GCTs, only choriocarcinoma cells reveal true positivity for PD-L1. These findings expand the realm of potentially targeted treatments for GCTs.